2013
DOI: 10.4103/0974-2077.118410
|View full text |Cite
|
Sign up to set email alerts
|

A study on fractional erbium glass laser therapy versus chemical peeling for the treatment of melasma in female patients

Abstract: Introduction:Melasma is a commonly acquired hypermelanosis and a common dermatologic skin disease that occurs on sun-exposed areas of face.Aims:To assess the efficacy and safety of non-ablative 1,550 nm Erbium glass fractional laser therapy and compare results with those obtained with chemical peeling.Materials and Methods:We selected 30 patients of melasma aged between 20 years and 50 years for the study. The patients were divided into two groups of 15 patients each. Group I patients were subjected to four se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Another study by Puri 96 assessed the difference between four sessions of 1550-nm erbium glass non-ablative fractional laser at 3-week intervals versus four sessions of 70% glycolic acid peels. Each treatment session involved four passes in one direction and four passes perpendicularly (eight passes in total) with a final density of approximately 2-2500 macroscopic treatment zones/cm 2 .…”
Section: Non-ablative 1550 Nm Fractional Lasermentioning
confidence: 99%
“…Another study by Puri 96 assessed the difference between four sessions of 1550-nm erbium glass non-ablative fractional laser at 3-week intervals versus four sessions of 70% glycolic acid peels. Each treatment session involved four passes in one direction and four passes perpendicularly (eight passes in total) with a final density of approximately 2-2500 macroscopic treatment zones/cm 2 .…”
Section: Non-ablative 1550 Nm Fractional Lasermentioning
confidence: 99%
“…Topical agents include hydroquinone, azelaic acid, kojic acid, retinoids, steroids, vitamin C (ascorbic acid), alpha‐tocopherylferulate, flavonoids, niacinamide, liquorice derivatives, and n‐acetyl‐4scysteaminylphenol . Lasers, especially nonablative fractional laser (NAFL) has been used for treatment of melasma . Positive effects of laser treatments may be equivalent to topical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Puri reported burning sensation (6.6%), erythema (10%), post inflammatory hyperpigmentation (13.3%) as the common adverse effects of peels. 14 We found that worsening of melasma was higher in the group treated with laser with 41.7% of patients developing post inflammatory hyperpigmentation. Transient erythema was observed in 37.5% of cases.…”
Section: Discussionmentioning
confidence: 64%